Penentuan Jalur Evakuasi dan Titik Kumpul Terhadap Bencana Gempa Bumi - Dwi Setyo Muyatno; Puryani Puryani; Yuli Dwi Astanti (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Universitas Pembangunan Nasional “Veteran” Yogyakarta (UPNVY) is one of the campuses that stand on the area of disaster prone areas. Based on the information from the head of facilities and infrastructure section, installation of evacuation route instructions and gathering points at UPNVY is based solely on the experience that has occurred several years ago.Earthquake disaster 2006 and Merapi eruption 2010 that occurs, many users of the building are confused in rescues themselves for lack of evacuation instructions.It is very vulnerable to the onset of loss or casualties because the earthquake disaster is unpredictable and occurs suddenly.This research aims to create visualization of user simulation against earthquake disaster.The simulation will also show you where to come out and save yourself as well as avoiding the dangerous places of the building quickly and securely with 3 scenarios. Simulated results for Pattimura building, Scenario 2 is considered best with the evacuation time of 46 ' 51 "with 2 classes passing through the middle stairs and 2 classes through the East and West Stairs.Meanwhile, Cipto Mangunkusumo building was selected scenario 2 with an evacuation time of 49 ′ with 2 class routes passing through the East Stairs and 1 class through the western stairs.The need for disaster information signage is 90 board class evacuation line, 76 board stair evacuation Line, 1 board gathering point, and 3 point gathering boards.